1993
DOI: 10.1136/oem.50.6.561
|View full text |Cite
|
Sign up to set email alerts
|

Further follow up of mortality in a United Kingdom oil distribution centre cohort.

Abstract: Results-of an extension of follow up (1976 to 1989) of a cohort of workers employed for at least one year between 1 January 1950 and 31 December 1975 at oil distribution centres in Britain are presented. Over 99%/o of the workers were successfully traced to determine their vital status at 31 December 1989. The mortality observed was compared with that expected from the death rates of all the male population of England and Wales. The mortality from all causes of death for the total study population was less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The general results from both studies are first described briefly [full details are given elsewhere (12,13,63,64)], followed by a report of the findings for kidney cancer and leukemia. Table 2 gives the observed and expected deaths, the SMR, and the 95% confidence interval for the SMR for all causes of death and all neoplasms for the total refinery and distribution center populations; separately for the first follow-up period, 1951-1975; the second follow-up period, 1976-1989; and the total follow-up period, .…”
Section: Mortality Resultsmentioning
confidence: 99%
“…The general results from both studies are first described briefly [full details are given elsewhere (12,13,63,64)], followed by a report of the findings for kidney cancer and leukemia. Table 2 gives the observed and expected deaths, the SMR, and the 95% confidence interval for the SMR for all causes of death and all neoplasms for the total refinery and distribution center populations; separately for the first follow-up period, 1951-1975; the second follow-up period, 1976-1989; and the total follow-up period, .…”
Section: Mortality Resultsmentioning
confidence: 99%
“…Exce ss risks for brain tumors have been associated with employment in petroleum refining (49). Finally, increa sed risks of kidney cancer , leukemia, and cancers of the larynx and prostate were found in a cohort of 23 306 British oil distribution workers (50).…”
Section: Resultsmentioning
confidence: 99%
“…Kemp et al (1980) suggested that a rise in the incidence of acute myeloid leukaemia between 1968-72 and 1973-77, shown in Scottish cancer registration data, was partly because of better diagnosis and partly because of a real increase, but not because of an improvement in registration. Bowie (1987) (Rushton and Alderson, 1983) and the second to 1989 (Rushton, 1993). In the second follow-up some excess mortality was found from leukaemia, in particular acute myeloid leukaemia, which has been associated in other studies with possible exposure to benzene (Vigliani, 1976;Brandt et al, 1978;Aksoy, 1989) …”
mentioning
confidence: 90%